Evangelical theology in transition theologians in dialogue with Donald Bloesch - Colyer, Elmer M., 1956- (Downers Grove, IL IVP, 1999)
Includes bibliiographical references and indexes.
Keywords: Bloesch, Donald G., -- 1928- , -- Evangelical theologian; Theology, doctrinal; Evangelicalism